Unraveling the intracellular trafficking mechanism of monocarboxylate transporter 1 in mammalian cells - Alves, Rosana Maria Abreu (2018)
Plasma membrane (PM) proteins, such as nutrient transporters and receptors, have a determinant role in the regulation of the overall cellular metabolism. They contribute to sensing, adhesion, signaling and nutrient uptake, allowing the cell to adapt and respond to distinct environmental cues. Rapid and dynamic regulation of PM proteins is achieved by means of selective endocytosis, where target proteins are internalized into endosomes and then they are either degraded or recycled back to the PM. This study focuses on monocarboxylate transporters (MCTs), which play essential metabolic roles in most tissues. These proteins are found to be upregulated in several cancer cell lines, displaying an enhanced glycolytic activity. MCTs contribute to fuel the metabolism of tumor cells, so reducing their expression can somehow starve cancer cells and make them more vulnerable to chemotherapy, opening new pathways for future therapies. We have previously generated several gene-edited cancer cell lines, known to express differently MCT transporters, using the CRISPR-Cas9 system (1). These cells will be applied to a combined microscopy platform (2) in the attempt to characterize the internalization dynamics of MCT transporters upon distinct environmental stimuli. This will be achieved by utilizing fluorescence optical sectioning microscopy obtained through aperture correlation microscopy with a Differential Spinning Disk (DSD) and nanomechanical mapping with an Atomic Force Microscope (AFM). An overview of the most significant results will be presented.